Simulators of mammary pathologies enclosed on a breast phantom for image quality control in mammography - Souza, Ivânia Ferreira; Nogueira, Luciana Batista; Campos, Tarcísio Passos Ribeiro (Scientia Plena, 2016)
This paper addresses the development of simulator of breast pathologies for image quality control in mammography. Simulators of neo density´s objects had been used for reproducing the breast pathologies. These objects had been adhered between two dental wax plates, inserted in an anthropomorphic and anthropometric compressed breast (AACB) phantom and submitted to radiological expositions. The AACB phantom is constituted of glandular, adipose and skin equivalent tissues, representing a fibro adipose breast with 50% of glandular and 50% adipose tissues. Radiographies of the AACB breast phantom were taken in the conventional and computerized systems. Two standard commercial breast phantoms referenced by the Brazilian College of Radiology and by the American College of Radiology were used as validation. After the expositions, qualitative image evaluation were carried through, identifying how many objects of the pathologies had been depicted, following the norms of quality control demanded by the Brazilian control agencies. The quality control measurements related to the pathology´s identifications, comparing with the standard breast phantoms, provided similar values. The simulating objects of mammary pathologies enclosed on the AACB phantom provide a suitable system for image quality control in mammography.